SOME OBSERVATIONS ON THE FISHERY AND BIOLOGY OF SARDINELLA FIMBRIATA (VAL.) AT VIZHINGAM - Bennet, P Sam (Indian Journal of Fisheries, 2011)
The sardines, Sardinella spp., constitute an important resource along the coasts of India. Commercial fishing in the inshore waters has shown that the different species of sardine are concentrated at different localities all along the coast. Thus the oil sardine Sardinella longiceps is localised along the Kerala and Mysore coasts. S. fimbriata occur in commercial quantities along the South Kerala and North Mysore coasts. S. albella is not abundant anywhere on the west coast, but at times occurs in small quantities along the coast. On the south-west coast S. clupeoides, along with 5. sirm and S. melanura forms a minor fishery during December (Bennet, 1965). All the six species have been caught in the inshore waters up to 10 km from the land. On the east coast of India S. fimbriata, S. albella, S. gibbosa and S. sirm occur in commercial quantities along the Madras and Andhra coasts. Other sardines occur only in small quantities.